Nathalie Stutzmann and Emőke Baráth sing Handel's ​Il Duello Amoroso Sablé-sur-Sarthe Baroque Festival 2016 - Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; et al. (CLC, 2016)
Contralto Nathalie Stutzmann leads her ensemble Orfeo 55 and, joined by Emőke Baráth--one of today's most exciting interpreters of the baroque repertoire for soprano!--they perform Il Duello Amoroso, an "imaginary opera" for two voices created out of a selection of arias and duos by Handel. Excerpts from some of the composer's best known operas like Rodelinda, Alcina, and Giulio Cesare alternate with those unearthed in some of his lesser known operatic gems like Scipione and Faramondo. The themes of love and passion are particularly eloquently portrayed in the music of this German composer who made his home in England, a man who was as brilliant a musician as he was a storyteller
Keywords: concert; Internet videos